APPLICATION OF THE LAW TO WOMEN WHO WORK AT NIGHTS ACCORDING TO LAW NO. 11 OF 2020 CONCERNING JOB COPYRIGHT: PENERAPAN HUKUM TERHADAP WANITA YANG BEKERJA MALAM HARI MENURUT UNDANG-UNDANG NO. 11 TAHUN 2020 TENTANG CIPTA KERJA - Yani Gea, Idah (UPMI Proceeding Series, 2023)
The results of the Law Concerning Job Creation are enacted in Law Number 11 of 2020 Concerning Job Creation. The purpose of this study is to compare the rights of women workers as regulated in Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation. This type of research is normative by taking data sources from related documents and then analyzing them so they can be understood. The protection for women's work referred to in the previous labor law is still valid and is not regulated in Law Number 11 of 2020 concerning Job Creation. So, it is certain that the workers' rejection during the process of the results of the Job Creation Law was incorrect and erroneous. The article that has undergone changes related to the protection of women workers does not at all change the substance of the protection of women workers as previously regulated through Law Number 13 of 2003 concerning Manpower.